Praktik Campur Kode Arab–Indonesia sebagai Konstruksi Identitas Santri dalam Kanal Youtube Jeda Nulis - Kholil, Mohammad Farhan; Maulana, Achmad Syafri; Pribadi, Mohammad (Study Program of Arabic Language Teaching, 2026)
This study analyzes Arabic-Indonesian code-mixing as a linguistic resource in the construction of santri (Islamic boarding school student) identity within the YouTube videos by Jeda Nulis and HAQIQI titled